2018
DOI: 10.1039/c8ee00415c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide in the cage: manganese metal–organic frameworks for high performance CO2electrodes in Li–CO2batteries

Abstract: Manganese MOF-based cathodes achieve high discharge capacity, reduced overpotentials and promoted reversibility in Li–CO2batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
155
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(161 citation statements)
references
References 50 publications
5
155
0
1
Order By: Relevance
“…The increased CO 2 adsorption capacity of TTCOF-Zn/Ni/Cu compared to the host TTCOF-2H should be attributed to the strong affinity between the metal ion and CO 2 molecule. [16] At the same time, water vapor adsorption tests for TTCOFs showed characteristic type II isotherm ( Figure S26-S29), which indicated that the internal pore structure and external surface of these materials are accessible to water. [17] This hydrophilicity fact can also be demonstrated by water contact angles tests showing angles of 22-458 ( Figure S30).…”
mentioning
confidence: 89%
“…The increased CO 2 adsorption capacity of TTCOF-Zn/Ni/Cu compared to the host TTCOF-2H should be attributed to the strong affinity between the metal ion and CO 2 molecule. [16] At the same time, water vapor adsorption tests for TTCOFs showed characteristic type II isotherm ( Figure S26-S29), which indicated that the internal pore structure and external surface of these materials are accessible to water. [17] This hydrophilicity fact can also be demonstrated by water contact angles tests showing angles of 22-458 ( Figure S30).…”
mentioning
confidence: 89%
“…However, these batteries still exhibited the low coulombic efficiency and huge voltage polarization over charge. Subsequently, Cu/C, Ru/C, metal–organic framework (MOF)/C, Ni‐based and Mo‐based catalytic cathodes have been applied in Li–CO 2 batteries, and the relatively enhanced coulombic efficiencies were obtained . Especially, He and co‐workers significantly improved the coulombic efficiency and cycle life of Li–CO 2 batteries by using Ru@Super P nanoparticles as the catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Later on, with 3D networks of carbon nanotubes (CNTs), Zhang et al achieved an improved cycling life of 29 cycles with controlled capacity of 1000 mAh g −1 at 50 mA g −1 . Very recently, metal–organic frameworks (MOFs) have been successfully introduced to Li‐CO 2 batteries with admirable performances . Typically, rechargeable Li‐CO 2 batteries use CO 2 as the active substance based on the electrochemical reaction of 4Li + 3CO 2 ↔ 2Li 2 CO 3 + C .…”
Section: Introductionmentioning
confidence: 99%